A green decontamination technology through selective biomineralization of algicidal microorganisms for enhanced astaxanthin production from Haematococcus pluvialis at commercial scale. (July 2021) - Yu, Byung Sun; Hong, Min Eui; Sung, Young Joon; Choi, Hong Il; Chang, Won Seok; Kwak, Ho Seok; Sim, Sang Jun
Graphical abstract: Highlights: Green decontamination tool was created to eliminate predators cidal to H. pluvialis. CBDS was conducted at mild alkalinity and low CaCl2 for non-calcifying H. pluvialis. CBDS showed an efficient removal of algicidal bacteria and fungi during cultivation. Astaxanthin production using CBDS was significantly enhanced in H. pluvialis. Large-scale outdoor astaxanthin production in H. pluvialis was improved by CBDS. Abstract: Currently, there is a lack of an efficient, environmentally-benign and sustainable industrial decontamination strategy to steadily achieve improved astaxanthin production from Haematococcus pluvialis under large-scale outdoor conditions. Here, this study demonstrates for the first time that a CaCO3 biomineralization-based decontamination strategy (CBDS) is highly efficient in selectively eliminating algicidal microorganisms, such as bacteria and fungi, during large-scale H. pluvialis cultivation under autotrophic and mixotrophic conditions, thereby augmenting the astaxanthin productivity. Under outdoor AT and MT conditions, the average astaxanthin productivity of H. pluvialis using CBDS in a closed photobioreactor system was substantially increased by 14.85- (1.19 mg L −1 d −1 ) and 13.65-fold (2.43 mg L −1 d −1 ), respectively, compared to the contaminated H. pluvialis cultures . Given the exponentially increasing demand of astaxanthin, a natural anti-viral, anti-inflammatory, and antioxidant drug, CBDS will be a technology of interest in H. pluvialis -based commercial astaxanthin production which has been hindered by the serious biological contaminations.